Extracellular Signal-Regulated Kinase (ERK) Activity During Sleep Consolidates Cortical Plasticity In Vivo - Dumoulin, Michelle C. (Cereb Cortex, 2015)
Ocular dominance plasticity (ODP) in the cat primary visual cortex (V1) is induced during waking by monocular deprivation (MD) and consolidated during subsequent sleep. The mechanisms underlying this process are incompletely understood. Extracellular signal-regulated kinase (ERK) is activated in V1 during sleep after MD, but it is unknown whether ERK activation during sleep is necessary for ODP consolidation. We investigated the role of ERK in sleep-dependent ODP consolidation by inhibiting the ERK-activating enzyme MEK in V1 (via U0126) during post-MD sleep. ODP consolidation was then measured with extracellular microelectrode recordings. Western blot analysis was used to confirm the efficacy of U0126 and to examine proteins downstream of ERK. U0126 abolished ODP consolidation and reduced both phosphorylation of eukaryotic initiation factor 4E (eIF4E) and levels of the synaptic marker PSD-95. Furthermore, interfering with ERK-mediated translation by inhibiting MAP kinase-interacting kinase 1 (Mnk1) with CGP57380 mimicked the effects of U0126. These results demonstrate that ODP consolidation requires sleep-dependent activation of the ERK-Mnk1 pathway.